2017
DOI: 10.1071/he16075
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor gyms and older adults – acceptability, enablers and barriers: a survey of park users

Abstract: Issue addressed Increasing the proportion of older adults meeting current recommendations for physical activity is important. This study aimed to determine the acceptability of outdoor gym use among older adults by assessing their outdoor gym use, intention to use, motivators, frequency and preference for use, and barriers and enablers to use. Methods Interviews were conducted with 438 consenting English speaking park users≥50 years after installation and promotion of an outdoor gym. Results Forty-two percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
0
26
1
1
Order By: Relevance
“…Outdoor exercise has been shown to improve mood and self‐esteem in older people where natural environments may have direct and positive impacts on wellbeing . Moreover, the use of outdoor gyms was reported as a potential equitable approach to engaging older adults in a variety of physical activity types . Consequently, exercising outdoors may increase enjoyment and provide social connectedness and support as reported with the use of the seniors’ exercise park and thus can lead to positive behaviour changes and sustained physical activity participation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outdoor exercise has been shown to improve mood and self‐esteem in older people where natural environments may have direct and positive impacts on wellbeing . Moreover, the use of outdoor gyms was reported as a potential equitable approach to engaging older adults in a variety of physical activity types . Consequently, exercising outdoors may increase enjoyment and provide social connectedness and support as reported with the use of the seniors’ exercise park and thus can lead to positive behaviour changes and sustained physical activity participation.…”
Section: Discussionmentioning
confidence: 99%
“…Group exercise can also be a good socialisation opportunity, with exercise sessions led by an allied health professional and administered via local community health organisations. Instructional exercise classes were identified previously as an important enabler by women to use outdoor gym equipment . This will introduce correct use of the equipment and exercise procedures, particularly for older people with comorbidities, as well as to provide an alternative for frail older people or those who prefer to be supervised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To some degree, this need is being met through the increasing availability of outdoor strength equipment, often situated in parks and other walking precincts (Sales, Polman, Hill, Karaharju-Huisman, & Levinger, 2015;Scott, Stride, Neville, & Hua, 2014). This form of strength training may be especially appealing to older people because of the connection with walking as a preferred form of exercise for this population (Stride, Cranney, Scott, & Hua, 2017). Gyms and fitness centers may learn from this development to create exercise environments that are more attuned to seniors' preferences, such as by providing outdoor components to exercise programs and finding alternatives to the loud music that is often a feature of modern centers.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies from non-European countries have shown that outdoor gyms mostly serve for adult and older adult groups. Outdoor gyms seem to be acceptable even for older adults according to an Australian study which showed that forty-two percent of park users above 50 years old had used an outdoor gym [ 44 ]. Outdoor gyms seem not only to be positively evaluated by users as pursuing health [ 45 ], but also to be used on a regular basis and thus raise the level of moderate to vigorous physical activity in parks [ 46 ].…”
Section: Discussionmentioning
confidence: 99%